MANAGEMENT BUSINESS OF CAPITAL LOAN SAVINGS BY VILLAGE OWNED ENTERPRISES IN SUKAMAJU VILLAGE, SUB-DISTRICT OF CIHAURBEUTI, DISTRICT OF CIAMIS: Array - Intan Nurmaesani; Neti Sunarti; Ii Sujai (Faculty of Social And Political Science Universitas Galuh, 2021)
Background of this research is motivated by the loaners who were not on time to repay loans, society’s assumed that government funds is an aid and did not need to be returned. The aims of this research; to determine the management business of capital loan savings, to known the obstacles that faced and efforts to overcome the obstacles in managing business of capital loan savings. Methodology of the research is used qualitative descriptive with 10 people of data sources. Technique collecting of the data used literature study and field study. Based on the research, it was found that: (a) management business of capital loan savings by Village Owned Enterprises has been good, it seen from good cooperation between administrators of Village Owned Enterprises, village government and society. Management has been done according to the management principle of village owned enterprises; (b) the obstacles faced were society’s delays in payment of business capital loans, the lack of capital provided; (c) the effort that made is to provide society’s understanding that fund given is a loan and it must be returned.